Manajemen Pelayanan Kesehatan Guna Kesiapan Jamaah Haji Kota Banda Aceh - Fakhruddin, Fakhruddin; Hasanah, Nurul; Habibi, Khairul (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2025)
Hajj pilgrimage is a mandatory pillar of Islam for Muslims who meet the requirements of physical, mental, and financial capability. This study aims to examine the health service management for prospective hajj pilgrims in Banda Aceh City, including physical examinations, vaccinations, and the utilization of health information systems based on applications such as SISKOHAT. The research method is qualitative descriptive with data collection through observation, interviews, and documentation. The results indicate that health service management plays a vital role in ensuring the physical and mental readiness of pilgrims to face the challenges of the Holy Land environment. An integrated health information system facilitates monitoring and reporting health conditions. Optimization of health services contributes to the smooth and successful implementation of the pilgrimage safely and devoutly. The Aceh Health Office continues to improve service quality through education and inter-agency collaboration.